Studying the Possibility of Optimizing the Statin Therapy Algorithm in Outpatient Practice - D. V. Nebieridze; N. M. Akhmedzhanov; S. A. Davitashvili; A. S. Lishuta; A. S. Safaryan (Рациональная фармакотерапия в кардиологии)
The high prevalence of lipid metabolism disorders in the Russian population and their contribution to cardiovascular risk require an optimization of their pharmacotherapy in clinical practice.Aim. To study the possible benefits of statin therapy in fixed doses for primary and secondary prevention of cardiovascular disease in outpatient practice.Material and methods. Ambulatory patients (n=300) with a high or very high risk with hypercholesterolemia who had indications for statin treatment for primary or secondary prevention of cardiovascular diseases were included into a non-randomized trial. Patients were divided into 2 groups. Group 1 had a titration regimen of statins in accordance with current recommendations (group 1A [n=50] – primary cardiovascular prevention; group 1B [n=100] – secondary cardiovascular prevention). Group 2 received a titration-free statin regimen in fixed doses (group 2A [n=50] – primary cardiovascular prevention; group 2B [n=100] – secondary cardiovascular prevention). Patients were prescribed atorvastatin (10-80 mg/day) or rosuvastatin (10-40 mg/day). Group 1 patients had visits to the doctor after 1, 3, 6 and 12 months from the start of statin use, group 2 patients – after 3 and 12 months. Laboratory studies included determination of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c). Changes in lipid levels, the frequency of reaching target TC and LDL-c levels were evaluated.Results. Titration-free statins treatment (Group 2) allowed reaching the target levels of TC and LDL-c after 12 months in 73.9% and 56.3% of patients, respectively. Significant changes were found after 3 months visit. In Group 1, these indicators were slightly lower (56.8% and 53.4%, respectively), while significant changes in the LDL-c level were found later than in Group 2. More than 50% of patients taking statins for secondary prevention, reached the target level of TC and LDL-c. At the same time, when using titration-free statin therapy, such results were recorded after 3 months. Patients taking statins for primary prevention achieved the TC target level in 95.7% of cases (subgroup 2A). The frequency of reaching the LDL-c target level in the subgroups of primary prevention was slightly lower.Conclusion. The use of a titration-free statin treatment regimen allowed to more effectively control of TC and LDL-c levels in patients with high and very high cardiovascular risk compared to the traditional statin therapy regimen, and to achieve target lipid levels earlier.